Physical Activity and Employee Well-Being among Employees during The Covid-19 Pandemic in Jakarta - Grasiaswaty, Novika; Putri, Qiftiyah Damiati (Fakultas Psikologi Universitas YARSI, 2024)
This study investigates the interrelation between physical activity and employee well-being during the COVID-19 pandemic in Jakarta. Drawing on existing literature, which predominantly links physical activity to health outcomes, this research aims to explore its correlation with employee well-being. Utilizing the International Physical Activity Questionnaire (IPAQ) and the Employee Well-Being (EWB) Scale, both translated into Indonesian, the study employed a correlation analysis to examine these dynamics. The findings indicate a statistically significant relationship between physical activity and employee well-being, with a correlation coefficient of r = 0.205 (p < 0.05). This research contributes to the broader understanding of physical activity's impact, extending beyond mere health benefits to encompass employee well-being, thus offering valuable insights for workplace health promotion strategies during unprecedented times like during the pandemic Covid-19.